FORMULASI TEPUNG KACANG HIJAU DAN TEPUNG TAPIOKA TERHADAP SIFAT SENSORI NUGGET IKAN SWANGGI (Priacanthus tayenus) Formulation of Mung Bean Flour and Tapioca Flour on Sensory Swanggi Fish (priacanthus tayenus) Nugget - Putri Utami, Sella; Astuti, Sussi; Herdiana, Novita; Sartika, Dewi (Jurusan Teknologi Hasil Pertanian, 2023)
The aim of the study was to obtain a formulation of mung bean flour and tapioca flour nugget swanggi fish (Priacanthus tayenus) with sensory properties according to SNI-7758-2013. The study was arranged in a Completely Randomized Block Design (RAKL) with one factor and four replications. The comparison treatment of tapioca flour and mung bean flour consisted of 6 levels, namely P1(100%:0%), P2(90%:10%), P3(80%:20%), P4 (70%:30%), P5(60%:40%), and P6(50%:50%). The similarity of data variance was analyzed by Bartlett's test and additional data by Tuckey's test, and then analysis of variance was carried out to determine the effect between treatments. The data were further analyzed with the Least Significant Difference Test (BNT) at the 5% level. The results showed that the best Swanggi fish nuggets, according to SNI 7758:2013, the addition of 30% mung bean flour and 70% tapioca flour (P4), which resulted in half-cooked nugget texture with a score of 7.07 (solid and compact) and nugget texture ripe with a score of 6.56 (somewhat dense and compact), taste with a score of 6.70 (typical of fish), the half-cooked aroma of nuggets with a score of 6.84 (like) and ripe nuggets with a score of 7.26 (like), colour with a score of 7.58 (yellowish white) and overall acceptance with a score of 7.92 (like). The water content of swanggi fish nuggets in the best treatment (P4) was 50.02%, ash content was 2.98%, protein content was 9.83%, and fat content was 4.17%.